Integrasi Pendidikan Pancasila di Pesantren: Tinjauan Yuridis terhadap UU Sistem Pendidikan Nasional - Zahwa Anzhella Pasya; Syarifah Annas Tasya; Juwita Widianingrum; Anis Muslikhah; Ahmad Mustain Nasoha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Islamic boarding schools (pesantren) play a strategic role in shaping the character, morality, and spirituality of the Indonesian nation as traditional Islamic educational institutions that have long contributed to social and religious life. Although their existence has been legally recognized through Law Number 18 of 2019 on Pesantren, the integration of Pancasila values into pesantren curricula continues to face several challenges, particularly in aligning these values with the provisions of the National Education System Law (UU Sisdiknas). This study aims to analyze the legal standing of pesantren within the national education system, identify opportunities and obstacles in implementing Pancasila Education in pesantren environments, and formulate policy recommendations that strengthen the internalization of national values. Using a normative juridical approach, this research examines national education regulations and religious education frameworks to understand the role of pesantren in supporting national development based on Pancasila. The findings of this study are expected to serve as a reference for the government, education stakeholders, and pesantren administrators in optimizing the role of pesantren as centers of character and civic development, as well as enhancing public understanding of the importance of harmonizing religious education with national civic education.